Spatial variability in soil available sulphur content in rubber growing regions of South India - Jessy M.D; Abraham T; Ambily K.K; Anilkumar K.S; Cyriac J; Eapen T; George S; Jacob J; Joseph P; Mathews P.M; Nair K.M; Philip A; et al. (PLACROSYM XXIII. Climate Resilient Technologies for Sustainability of Plantation Crops, 6-8 March 2019, Central Coffee Research Institute, Chikkamangaluru, Karnataka, India, Abstracts, p.81.)
Delineation of spatial variability in soil fertility parameters is of critical importance to identify fertility constraints of a given site and for effective soil resource management. In India, rubber is cultivated in regions varying in physiography, climate and soil properties and the soil fertility will also vary at different spatial scales. In this article, the spatial variability in available S status in rubber growing regions of South India is presented. Geo-referenced soil samples were collected from rubber growing regions of South India, analyzed following standard analytical protocol and the available S status was mapped geostatistically following kriging interpolation technique. Wide spatial variability, both intra and inter region was observed in soil available S status. In general, rubber growing regions in North Kerala, Karnataka, Goa and Maharashtra were low in available S status. S nutrition of rubber has not received adequate attention so far and these maps identify regions which need special attention with respect to S nutrition, for conducting response/case studies and surveys for future crop husbandry.
Keywords: Rubber growing soil; Soil fertility; Spatial variability; Sulphur content